1991
DOI: 10.1002/chir.530030615
|View full text |Cite
|
Sign up to set email alerts
|

Production of a chiral polyester by Pseudomonas oleovorans grown with 5‐phenyl‐2,4‐pentadienoic acid

Abstract: Pseudomonas oleovorans has been previously shown to produce a polyester containing a phenyl pendant group when grown with 5-phenylpentanoic acid under nutrientlimiting conditions. The same polyester was produced when 5-phenyl-2,4-pentadienoic acid was the only carbon source, and a mixture of two different polymers was produced when this bacterium was grown on a mixture of 5-phenyl-2,4-pentadienoic acid and nonanoic acid. The polymer blend obtained was separated by fractional crystallization to yield poly(3-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 6 publications
2
9
0
Order By: Relevance
“…In numerous literature reports, the aromatic PHAs have been studied widely. Properties such as degradability (Olivera et al, 2001 ), surface structure (Takagi et al, 2004 ), solubility (Mizuno et al, 2017 ), and thermal behavior (Antoun et al, 1991 ) have been assessed, and their dependency on the polymer's structure was identified (Ishii-Hyakutake et al, 2018 ).…”
Section: Trends Unveiledmentioning
confidence: 99%
“…In numerous literature reports, the aromatic PHAs have been studied widely. Properties such as degradability (Olivera et al, 2001 ), surface structure (Takagi et al, 2004 ), solubility (Mizuno et al, 2017 ), and thermal behavior (Antoun et al, 1991 ) have been assessed, and their dependency on the polymer's structure was identified (Ishii-Hyakutake et al, 2018 ).…”
Section: Trends Unveiledmentioning
confidence: 99%
“…Generally, to generate aromatic PHAs, defined compounds containing aromatic groups are added to the medium as a precursor (i.e., 5PhV or 5-phenyl-2,4-pentadienoic acid is used as a precursor to produce PHAs containing 3H5PhV [14,15,19,20]). However, there are a few reports on the production of aromatic PHAs without any supplementation with these defined aromatic compounds [16,18].…”
Section: Biosynthesized Phas Bearing Aromatic Groups As Side Chainsmentioning
confidence: 99%
“…The same polymer was obtained when P. putida BM01 [19] or P. putida KT2440 [15] was used as the PHA production host. It was reported that the P(3H5PhV) homopolymer was also produced from 5-phenyl-2,4-pentadienoic acid by P. oleovorans [20] and from 7PhV or 9PhN by P. putida U [25]. In the latter case, the 3H5PhV monomer would be generated through the β -oxidation cycle.…”
Section: Biosynthesized Phas Bearing Aromatic Groups As Side Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several aromatic pendant groups with different functionalities, such as phenyl, phenoxy, methyphenyl, methylphenoxy, nitrophenyl, cyanophenoxy, fluorophenoxy, thiophenoxy, and benzoyl groups, have been incorporated into aromatic PHAs . However, only P­(3H5PhV) ,− and poly­(3-hydroxy-6-phenylhexanoate) have been biosynthesized as homopolymers, while all other aromatic PHAs have been incorporated as copolymers with P3HB or other aromatic groups.…”
Section: Introductionmentioning
confidence: 99%